Osteoporosis regulation by salubrinal through eIF2α mediated differentiation of osteoclast and osteoblast - He, Long (2012)
Nuclear factor-κB (NF-κB) ligand (RANKL) was shown to induce osteoclast differentiation by increasing the expression of c-Fos, NFATc1 and TRAP. Salubrinal treatment to bone marrow macrophage (BMM) cells, however, significantly blocked NFATc1 expression and osteoclast differentiation by RANKL. Overexpression of NFATc1 further confirmed that NFATc1 is a key factor affected by salubrinal in osteoclast differentiation by RANKL. Unexpectedly, NFATc1 and c-Fos mRNA expressions were not affected by salubrinal, implicating that NFATc1 expression is regulated at a translational stage. In support of this, salubrinal increased the phosphorylation of a translation factor eIF2α, decreasing the global protein synthesis including NFATc1. In contrast, a phosphorylation mutant plasmid pLenti-eIF2α-S51A restored RANKL-induced NFATc1 expression and osteoclast differentiation even in the presence of salubrinal. Furthermore, knockdown of ATF4 significantly reduced salubrinal-induced osteoblast differentiation as evidenced by decreased calcium accumulation and lowered expressions of the osteoblast differentiation markers, alkaline phosphatase and RANKL in MC3T3-E1 osteoblast cells. Salubrinal treatment to co-cultured BMM and MC3T3-E1 cells also showed reduction of osteoclast differentiation. Finally, salubrinal efficiently blocked osteoporosis in mice model treated with RANKL as evidenced by elevated bone mineral density (BMD) and other osteoporosis factors. Collectively, our data indicate that salubrinal could affect the differentiation of both osteoblast and osteoclast, and be developed as an excellent anti-osteoporosis drug. In addition, modulation of ATF4 and NFATc1 expressions through eIF2α phosphorylation could be a valuable target for the treatment of osteoporosis.